Novel approaches to diagnosis of viral infections - Lipkin, W. Ian (Henry Stewart Talks, 2019)
Introduction to microbial discovery, surveillance and diagnosis, Koch’s Postulates and proof of causation, Mechanisms of microbial pathogenesis, Gene:environment interactions, Molecular and serological assays for differential diagnosis of infectious diseases, High throughput sequencing, Future perspectives